Investigating the Effect of Intercritical Annealing Heat Treatment on the Quenching and Partitioning of Ferrite-Bainite-Martensite Microphases in High-Silicon Low-Alloy DIN 1.5025 Steel - Shima Pashangeh; Soheil Afkhami; Seyyed Sadegh Ghasemi Banadkouki (مواد نوین, 2023)
Abstract In this study, the influence of intercritical annealing heat treatment on the quenching and partitioning (Q&P) of ferrite-bainite-martensite multiphase in high-silicon low-alloy DIN 1.5025 steel was investigated. Initially, a normalization heat treatment process involving austenitization at 900°C for 5 minutes followed by air cooling to room temperature was conducted to achieve homogeneous and uniform initial ferritic-pearlitic microstructures for all of the specimens. Subsequently, the Q&P heat treatment cycles comprising partial austenitization in the intercritical austenite-ferrite region at 775°C for 60 minutes, followed by quenching in a molten salt bath of partitioning at temperatures of 250, 300, and 350°C for various durations of 2, 5, 15, 30, and 60 minutes were performed. Optical microscopy (OM) and field-emission scanning electron microscopy (FE-SEM) observations, standard tensile tests, and hardness measurements were employed to evaluate the microstructural changes in relation to the mechanical properties of the specimens. The results demonstrate that the presence of ferrite phase during partial austenitization in the intercritical austenite-ferrite region enriches austenite with carbon, reduces the martensite start temperature (Ms), promotes the formation of fine bainite crystals, and consequently leads to unconventional continuous yield behavior in the specimens. A partitioning heat treatment time of 30 minutes in the molten salt bath at 350°C induces the formation of multiphase microstructures containing a mixture of ferrite-bainite-martensite microphases, along with optimizing the formability and tensile strength properties to values of 16% and 1350 MPa, respectively.